A functional analysis framework for modeling, estimation, and control in science and engineering - Banks, H. Thomas (Boca Raton : CRC Press, 2012)
'The result of lecture notes from courses the author has taught in applied functional analysis beginning in the late 1980s through the present, the choices of topics covered here are not purported to be comprehensive and even border on the eclectic. In contrast to classical PDE techniques, functional analysis is presented as a basis of modern partial and delay differential equation techniques. It is also somewhat different from the emphasis in usual functional analysis courses where functional analysis is a subdiscipline in its own right. Here it is treated as a tool to be used in understanding and treating distributed parameter systems'--
Includes bibliographical references and index.
Keywords: Functional analysis; Science -- Mathematical models; Engineering -- Mathematical models